PET and SPECT Tracer Development via Copper-Mediated Radiohalogenation of Divergent and Stable Aryl-Boronic Esters - Austin Craig; Frederik J. Sachse; Markus Laube; Florian Brandt; Klaus Kopka; Sven Stadlbauer (Pharmaceutics)
Background/Objectives: Positron emission tomography (PET) and single-photon emission computed tomography (SPECT) are highly sensitive clinical imaging modalities, frequently employed in conjunction with magnetic resonance imaging (MRI) or computed tomography (CT) for diagnosing a wide range of disorders. Efficient and robust radiolabeling methods are needed to accommodate the increasing demand for PET and SPECT tracer development. Copper-mediated radiohalogenation (CMRH) reactions enable rapid late-stage preparation of radiolabeled arenes, yet synthetic challenges and radiolabeling precursors’ instability can limit the applications of CMRH approaches. Methods: A series of aryl-boronic acids were converted into their corresponding aryl-boronic acid 1,1,2,2-tetraethylethylene glycol esters [ArB(Epin)s] and aryl-boronic acid 1,1,2,2-tetrapropylethylene glycol esters [ArB(Ppin)s] as stable and versatile precursor building blocks for radiolabeling via CMRH. General protocols for the preparation of 18F-labeled and 123I-labeled arenes utilizing CMRH of these substrates were developed and applied. The radiochemical conversions (RCC) were determined by radio-(U)HPLC. Results: Both ArB(Epin)s and ArB(Ppin)s-based radiolabeling precursors were prepared in a one-step synthesis with chemical yields of 49–99%. Radiolabeling of the aryl-boronic esters with fluorine-18 or iodine-123 via CMRH furnished the corresponding radiolabeled arenes with RCC of 7–99% and 10–99%, respectively. Notably, a radiohalogenated prosthetic group containing a vinyl sulfone motif was obtained with an activity yield (AY) of 18 ± 3%, and applied towards the preparation of two clinically relevant PET tracers. Conclusions: This approach enables the synthesis of stable radiolabeling precursors and thus provides increased versatility in the application of CMRH, thereby supporting the development of novel PET and SPECT radiotracers.